Design: the answer of contemporary businesses to the requirements of sustainable development - Rodica Pamfilie; Roxana Procopie; Magdalena Bobe; Smaranda Visan (Amfiteatru Economic Journal, 2013)
This paper presents a conceptual model showing the involvement of design in the development of sustainable businesses, based on the analysis and synthesis of scientific research undertaken and the results published by the authors during the last decade. The starting point is the consumer with his needs, hopes and ideals related to the quality of products and services. Customer satisfaction is the priority goal of economic activities carried out to improve the quality of life while guiding modern corporate strategies. Creators, consumers and managers understand and pursue the same objectives related to conservation of material resources, minimizing energy consumption and improving the environmental impact of waste. Rethinking concepts, developing ecological projects and products, modern companies use sustainable design to accommodate environmental criteria but also to give ethical, social and environmental meaning to their actions, or in other words, to develop responsible business. Accepting the major influence that design has on the quality of life and the environment, the study undertaken aims to highlight this concern in the case of manufacturing companies by presenting the consumer's reaction to their products. With the conceptual model as theoretical background, an appropriate questionnaire was developed and applied, with the purpose of demonstrating the significant contribution of design in making businesses meet the needs of sustainable development.
Keywords: L15; M10; Q01; Q56; 330; consumer; responsible business; innovative design; sustainable design; sustainable development